Pengenalan Penggunaan Media Sosial Sebagai Sarana Untuk Memasarkan Produk Kepada Mitra UMKM - Rayi Retno Dwi Asih; Faisal, Aekram; Hermi (Dirkantara Indonesia, 2024)
The impact of the pandemic has been felt in all aspects of life, especially the economy in Indonesia. There are many business sectors that have been forced out of business because they are unable to deal with the brunt of this deadly virus. As time goes by, conditions that are getting better after the pandemic require entrepreneurs to start opening their businesses again. The existence of positive opportunities makes MSME actors have enormous potential to be successful in the market, if they can adopt the right marketing strategy. The SME group in the Depok area, to be precise, the Azalea Grand Depok City Sector, have started learning to build small businesses in local residential areas. Before this activity was carried out, several participants were recorded as not having Social Media accounts, not even using Social Media for their product marketing activities. After this activity was held, it was discovered that 90% of the Counseling and Training participants had Social Media Accounts, 90% had Instagram/Tiktok accounts, 80% used their accounts to promote their products, and 95% stated that the counseling and training was useful for them.